2015
DOI: 10.1021/acsami.5b04490
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Stability of Perovskite Solar Cells to Moisture by the Facile Hydrophobic Passivation

Abstract: In this study, a novel and facile passivation process for a perovskite solar cell is reported. Poor stability in ambient atmosphere, which is the most critical demerit of a perovskite solar cell, is overcome by a simple passivation process using a hydrophobic polymer layer. Teflon, the hydrophobic polymer, is deposited on the top of a perovskite solar cell by a spin-coating method. With the hydrophobic passivation, the perovskite solar cell shows negligible degradation after a 30 day storage in ambient atmosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
230
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(235 citation statements)
references
References 28 publications
5
230
0
Order By: Relevance
“…A recent study by Karunadasa et al demonstrated the enhanced moisture stability of a layered 2D hybrid perovskite [25], in which phenylethylamine (PEA) not only acts as a molecule for tuning the spacing between the perovskite layers toward higher bandgap, but also provides the perovskite absorber with a hydrophobic surface, which leads to increased durability. Yong et al introduced a simple and effective passivation method to overcome water vulnerability for the perovskite solar cell [26]. By coating a hydrophobic polytetrafluoroethylene (PTFE) layer onto the top surface of the cell, water diffusion into the perovskite cell was effectively blocked and the solar cell exhibited a significantly enhanced stability under the ambient atmosphere conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Karunadasa et al demonstrated the enhanced moisture stability of a layered 2D hybrid perovskite [25], in which phenylethylamine (PEA) not only acts as a molecule for tuning the spacing between the perovskite layers toward higher bandgap, but also provides the perovskite absorber with a hydrophobic surface, which leads to increased durability. Yong et al introduced a simple and effective passivation method to overcome water vulnerability for the perovskite solar cell [26]. By coating a hydrophobic polytetrafluoroethylene (PTFE) layer onto the top surface of the cell, water diffusion into the perovskite cell was effectively blocked and the solar cell exhibited a significantly enhanced stability under the ambient atmosphere conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[ 28,29 ] However, the modifi cation of the neat iodide perovskite absorber with layered structure, [ 23,25 ] pseudo halide, [ 24 ] or bromide counterparts [ 22 ] usually lead to the deterioration of the performance with a PCE lower than 10%. Other studies were based on devices showing moderate performance (<15%).…”
mentioning
confidence: 99%
“…Hwang et al showed that they could also improve the performance lifetime of a device by spinning a layer of amorphous Teflon on top of the device. 98 Chang et al use the concept of a dense alumina layer as protective barrier and show that the atomic layer deposition of an Al 2 O 3 layer significantly improves the air-stability due to the very low oxygen and water vapor transmission of the barrier layer. 99 More challenging is the device encapsulation for devices on flexible substrates.…”
mentioning
confidence: 99%